2013
DOI: 10.1074/jbc.m113.481622
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide 1-Phosphate Mediates Endothelial Cell Invasion via the Annexin a2-p11 Heterotetrameric Protein Complex

Abstract: Background: Extracellular ceramide 1-phosphate is presumed to interact with extracellular proteins to mediate cellular invasion. These proteins are unidentified. Results: C-1-P interacts with both annexin a2 and p11 proteins. C-1-P-mediated vascular endothelial cell invasion requires expression of these proteins. Conclusion: Extracellular C-1-P mediates invasion via an interaction with the annexin a2-p11 heterotetramer. Significance: Gradients of C-1-P may guide vascular endothelial cell invasion during wound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 66 publications
3
27
0
Order By: Relevance
“…C1P might exert its anti-inflammatory capacity by suppressing the activation of the NF-κB pathway. We support the argument of Hankins et al (7, 18, 58) that fluctuations in C1P levels determine its proinflammatory or anti-inflammatory effects, and further studies are required to clarify the interaction of C1P with the plasma membrane or possible delineated receptors, as well as the effect of C1P in specific cell types. C1P can act either as an intracellular second messenger (10) or as an extracellular mediator binding to functionally identified, but still not cloned, specific G protein–coupled receptor upon secretion to the extra-cellular milieu (11).…”
Section: Discussionsupporting
confidence: 86%
“…C1P might exert its anti-inflammatory capacity by suppressing the activation of the NF-κB pathway. We support the argument of Hankins et al (7, 18, 58) that fluctuations in C1P levels determine its proinflammatory or anti-inflammatory effects, and further studies are required to clarify the interaction of C1P with the plasma membrane or possible delineated receptors, as well as the effect of C1P in specific cell types. C1P can act either as an intracellular second messenger (10) or as an extracellular mediator binding to functionally identified, but still not cloned, specific G protein–coupled receptor upon secretion to the extra-cellular milieu (11).…”
Section: Discussionsupporting
confidence: 86%
“…In addition, binding of C1P to the N-terminal lipid binding C2 domain of cPLA2-a was required for stimulation of this enzyme activity leading to the production of arachidonic acid and subsequent generation of prostaglandins . Moreover, it was recently reported that C1P binds the annexin a2/p11 heterotetrameric protein complex to elicit endothelial cell invasion (Hankins et al, 2013). The latter observation is consistent with our previous work showing that C1P potently stimulates macrophage migration Granado et al, 2009b).…”
Section: C1p Biologysupporting
confidence: 91%
“…For cellular transport of C1P the recently identified C1P transport protein was shown to recognize the acyl amide moiety of C1P (Simanshu et al 2013), an interaction that may also provide selectivity for some sphingolipids when compared to their glycerophospholipid counterparts. Additionally, annexin A2 which has long been known to bind PS and PI(4,5)P 2 was recently shown to bind C1P with even higher affinity than that of PS or PA (Hankins et al 2012). Other proteins have also recently been identified that bind ceramide (Saddoughi et al 2013) as well as phosphorylated sphingolipids (Lamour et al 2011).…”
Section: Phosphoinositide-bindingmentioning
confidence: 99%